Improvement of Music Teachers’ Competence via Productive Activity - Sile, Maruta; Ratniece, Inta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Professional pedagogical performance is an important condition for a successful implementation of national education policy. Creative and understanding the evolving process of today – a competent music teacher is competitive both in the domestic employment market and abroad. Music as art is creative in its essence. However, in practice it is often found that reproductive activity often dominates the preparation of music teachers. Being the most creative of arts – music in the course of acquiring the art of playing music loses its inherent creativity. Primarily, the preparation of music teachers is focused on activities based on the quality of learning by heart and remembering. The matter of research is related to raising awareness of productive activity in the improvement of music teacher competency. The objective is to study opportunities for improvement of music teacher competences within productive activity. The research is developed by theoretical and empirical methods involving discussions and a questionnaire. In order to improve the professional competence of a music teacher via productive activity, a procedural – structural model titled “Improvement of Music Teacher’s Competence via Improvisation” was developed, the utility of which is evaluated on the basis of various specific criteria. An exercise system is also developed and approved. As a result of verifying the model, we assure the utility thereof in the improvement of the professional competence of music teachers. The developed improvisation exercises are useful for practical productive activities.